Pengaruh Kualitas Pelayanan Pendidikan Terhadap Kepuasan Peserta Didik Kelas VIII di Madrasah Tsanawiyah Unwaanunnajah - Awalia, Nadia Rizki; Muhtadi, Mohammad; Nurhidayat, Arif (Lembaga Yasin AlSys, 2025)
This study is motivated by the limited research on the relationship between the quality of educational services and student satisfaction, despite this phenomenon significantly impacting the learning experience in Islamic educational institutions. The aim of this research is to measure the effect of the quality of educational services on the satisfaction of eighth-grade students at MTs Unwaanunnajah. This study employed a quantitative approach with a survey design, involving 78 respondents selected using saturated sampling technique. Data were collected through a questionnaire and analyzed using SPSS version 29, with validity tests, reliability tests (Alpha Cronbach), normality tests, linearity tests, and simple linear regression analysis. The results indicate a positive and significant effect of the quality of educational services on student satisfaction, with an F value of 26.734 (p < 0.001) and a correlation coefficient of 0.510, which is categorized as moderate. The coefficient of determination (R²) value of 0.260 indicates that 26.0% of student satisfaction is influenced by the quality of educational services, while the remaining 74.0% is influenced by other variables. These findings support the objectives of the research and reinforce the theory that dimensions of service quality, which include responsiveness, assurance, tangibility, empathy, and reliability, play a crucial role in shaping student learning satisfaction. The main conclusion of this study is that improving the quality of educational services can enhance student satisfaction. The implications of this research include theoretical contributions to enriching the literature on the quality of Islamic educational services, as well as practical recommendations for school management to continuously improve service quality. This study also opens opportunities for further research with a broader scope and comparisons across institutions.